ASSURANCE OF STRUCTURAL STEEL SURVIVABILITY BASED ON RESERVATION OF PRODUCTION FACILITIES CORROSION PROOFNESS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper deals with the task of selecting quality and reliability indices of means and methods of corrosion protection considering structural strength requirements. Systematized description of standard (basic, characteristic) impacts and representative values of negative corrosiveness factors is provided. For corrosion protection design, classification features of steel structures and their protective coatings based on criticality rating are specified. Design indices of structural steel durability are discussed. The developed methodology involves an analytical–experimental estimate of reliability and availability factors of corrosion protection. Logistical system has been generated for reserve planning of survivability of structure on the basis of corrosion proofness signs. A method is proposed for calculating compensation for corrosion losses when comparing competitive advantages of corrosion protection systems. The index of corrosion protection level is specified for managing process safety on the basis of risk reduction.
Keywords: reliability; structural and process safety; survivability; corrosion hazard; risk assessment